Path-Following Control Method for Surface Ships Based on a New Guidance Algorithm - Zhanshuo Zhang; Yuhan Zhao; Guang Zhao; Hongbo Wang; Yi Zhao (Journal of Marine Science and Engineering, 2021)
A new type of path-following method has been developed to steer marine surface vehicles along desired paths. Path-following is achieved by a new hyperbolic guidance law for straight-line paths and a backstepping control law for curved paths. An optimal controller has been improved for heading control, based on linear quadratic regulator (LQR) theory with nonlinear feedback control techniques. The control algorithm performance is validated by simulation and comparison against the requirements of International Standard IEC62065. Deviations are within the allowable range of the standard. In addition, the experimental results show that the proposed method has higher control accuracy.